Estimating correlations with censored data. Issue Volume 32:Issues 3(2020) (2nd July 2020) - Weaver, Brian P.; Kaufeld, Kimberly; Warr, Richard
KEY POINT: Including censored observations, when estimating correlations, has a nontrivial impact on the analysis.